Políticas do vestir: recortes em viés - Mesquita, Cristiane (2008)
Inspired by the rituals of the conceptual character Jardelina Da Silva, this thesis aims to delineate cuts on the lines of forces that crosses on vestiments flows and the appearance composition in different perspectives, approaches and conceptual boardings. Taking the zigzag movement as a research method and a writing strategy, our journey initiates by the documentary Jardelina da Silva, me myself. In this text, we will be in her company in the first part, covering concepts as well as schizo, ressonating body, line of flight, becoming, event, territory and style. We proceed in the second part examining other cuts for the concept of style, emphasising it as the strongest operator for the fashion machine, main scenario of the vestiments flows market in connection with the body. In this context, we punctuate the body as a subjective constitution locus and investigate the style under diferent aspects. The third part explores ways of relation and production of senses in the field of encounters constituted by dressing. Finally, we present as a way out zigzag movements, some works selected in the art field, crossing the questions delineated and covered in this thesis. All the journey is pervaded by the theories of the philosopher Gilles Deleuze and the psychoanalyst Felix Guattari s and by other voices, as well as Suely Rolnik, Peter Pál Pelbart, Luis Orlandi, Michel Foucault, Jurandir Freire Costa, Maurizio Lazzarato, Patrice Bollon, Denise Bernuzzi de Sant' Anna, Rosane Preciosa and Peter Stallybrass, among others